The barbed-wire college : reeducating German POWs in the United States during World War II - Robin, Ron Theodore (Princeton, N.J. : Princeton University Press, 1995)
From Stalag 17 to The Manchurian Candidate, the American media have long been fascinated with stories of American prisoners of war. But few Americans are aware that enemy prisoners of war were incarcerated on our own soil during World War II. In The Barbed-Wire College Ron Robin tells the extraordinary story of the 380,000 German prisoners who filled camps from Rhode Island to Wisconsin, Missouri to New Jersey. Using personal narratives, camp newspapers, and military records, Robin re-creates in arresting detail the attempts of prison officials to mold the daily lives and minds of their captives. From 1943 onward, and in spite of the Geneva Convention, prisoners were subjected to an ambitious reeducation program designed to turn them into American-style democrats. Under the direction of the Pentagon, liberal arts professors entered over five hundred camps nationwide. Deaf to the advice of their professional rivals, the behavioral scientists, these instructors pushed through a program of arts and humanities that stressed only the positive aspects of American society. Aided by German POW collaborators, American educators censored popular books and films in order to promote democratic humanism and downplay class and race issues, materialism, and wartime heroics. Red-baiting pentagon officials added their contribution to the program, as well; by the war's end, the curriculum was more concerned with combating the appeals of communism than with eradicating the evils of National Socialism. But the reeducation officials neglected to account for one factor: an entrenched German military subculture in the camps, complete with a rigid chain of command and a propensity for murdering "traitors." The result of their neglect was utter failure for the reeducation program. By telling the story of the program's rocky existence, however, Ron Robin shows how this intriguing chapter of military history was tied to two crucial episodes of twentieth-century American history: the battle over the future of American education and the McCarthy-era hysterics that awaited postwar America
Ch. 1 The Genesis of Reeducation 17 -- Ch. 2 The POW Camp and the Total Institution 30 -- Ch. 3 Professors into Propagandists 43 -- Ch. 4 The Idea Factory and Its Intellectual Laborers 59 -- Ch. 5 Der Ruf: Inner Emigration, Collective Guilt, and the POW 75 -- Ch. 6 Literature: The Battle of the Books 91 -- Ch. 7 Film: Mass Culture and Reeducation 107 -- Ch. 8 Politics and Scholarship: The Reeducation College 127 -- Ch. 9 The Democracy Seminars: Preparation for "One World" 145 -- Ch. 10 Variations on the Theme of Reeducation 162 -- Ch. 11 Reeducation and the Decline of the American Dons 180.
Includes bibliographical references (pages 189-211) and index.
Print version record.
eBooks on EBSCOhost
Keywords: World War, 1939-1945 -- Prisoners and prisons, American; World War, 1939-1945 -- Education and the war; World War, 1939-1945 -- United States; World War, 1939-1945 -- Psychological aspects; Prisoners of war -- Germany -- History -- 20th century; Prisoners of war -- United States -- History -- 20th century; Education, Higher -- United States -- History -- 20th century; Social sciences -- United States -- History -- 20th century; Education, Humanistic -- United States -- History -- 20th century; Guerre mondiale, 1939-1945 -- Éducation et guerre; Guerre mondiale, 1939-1945 -- États-Unis.; Guerre mondiale, 1939-1945 -- Aspect psychologique; Prisonniers de guerre -- Allemagne -- Histoire -- 20e siècle.; Éducation humaniste -- États-Unis -- Histoire -- 20e siècle.; HISTORY -- Military -- World War II; Education, Higher; Education, Humanistic; Prisoners of war; Psychological aspects; Social sciences; War and education; Germany; United States; 1900 - 1999; World War 2 -- Prisoners of war; United States; History